Standardization of Kharif Onion Cultivars - Tripathy, P.; Sahoo, B. B.; Priyadarshini, A.; Das, S. K.; Dash, D. K. (International Journal of Bio-resource and Stress Management, 2023)
A field investigation was conducted to evaluate the cultivars of onion for bulb yield and reactions to pests and diseases during kharif season at AINRP on Onion & Garlic, College of Horticulture (OUAT), Sambalpur, and Odisha, India. Twenty two cultivars of onion including five national check varieties supplied by Directorate of Onion & Garlic Research, Rajgurunagar, Pune were evaluated by adopting RBD with three replications. Results revealed significantly better leaves plant-1 (8.87), collar thickness (1.44 cm), average bulb weight (70.44 g), polar diameter (6.44 cm), equatorial diameter (4.53 cm) having better TSS (10.76%), tolerance to thrips infestation (2.36 thripsplant-1), marketable bulb yield ( 223.65 q ha-1) and total bulb yield (276.96 q ha-1) were recorded for NRCWO-3, closely followed by Bhima Super, NRCRO-1, NRCWO-4 and the check, Bhima Red than rest of the entries tested. However, significantly heaviest bulb weight of 78.68g was recorded in entry, VG-18. Similarly during kharif season more than 200 q ha-1 marketable bulb yield was recorded in the entries like NRCWO-3 (223.65 q ha-1), Bhima Red (215.04 q ha-1), NRCWO-1 (212.58 q ha-1), NRCWO-4 (208.60 q ha-1) and NRCWO-2 (205.54 q ha-1). On the other hand, total bulb yield of more than 200 q ha-1 was recorded in entry, NRCWO-3 (276.94 q ha-1), Bhima Red (268.09 q ha-1), NRCWO-4 (259.66 q ha-1), NRCWO-2 (249.63 q ha-1), Bhima Super (249.35 q ha-1), NRCWO-1 (248.61 q ha-1) and NRCRO-3 (242.96 q ha-1). Thus, the varieties like NRCWO-1, NRCWO-3. NRCWO-4, Bhima Super, Bhima Red and NRCRO-3 may be recommended for karif season cultivation to obtain maximum bulb yield. Similarly cultivars like Bhima Kiran, Bhima Super, NRCRO-2 and Col-652 may be recommended for better tolerance to both Purple Blotch and Thrips infestation.